TheoMedia : the Media of God and the Digital Age. - Byers, Andrew (The Lutterworth Press, 2014)
This book is a hermeneutical project in the church's wider efforts of trying to understand the technological mediascape of the twenty-first century. The purpose is not to offer a how-to guidebook to help churches incorporate communications technology into their worship and witness. Byers provides something more foundational, the beginnings of a way of constructing a theological frame of reference for understanding and appropriating media in the digital age and in the ages to come.